PERANCANGAN KONSEP MODULAR PRODUCTION SYSTEM (MPS) DENGAN MENGGUNAKAN METODE VDI 2221 DAN ANALISIS KONSUMSI ENERGI PADA SISTEM PRODUKSI MODULAR (MPS) - ALian Jaya Lesmana; Agus Halim; Didi Widya Utama (Jurnal Mitra Teknik Industri, 2026)
This study aims to design a modular production system (MPS) concept that is capable of optimally lifting and moving workpieces and analysing the energy consumption required during operation. The method used is VDI 2221 for systematic concept design, combined with a sensor-based quantitative experimental method to measure air and electrical energy consumption. The design results produce four concept variations, with variation 4 (4-axis robot, specific gripper bracket, magnetic sensor, electric gripper, aluminium profile as bed plate, table, steel foot adjuster, PLA+ jaw gripper) selected as the best concept because it is in accordance with the initial specification list and has the highest weight value (4.54). Pneumatic energy consumption over one hour recorded a total air volume of 338 L, a converted power of 1.16 kW, and a total energy of 4,175.424 kJ. Total electrical energy consumption reached 0.315 kWh, with the compressor accounting for the largest share at 0.239 kWh. The VDI 2221 method proved effective in producing a systematic MPS design concept that fulfils all established technical specifications.